PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL UNTUK MENANGGULANGI RADIKALISME DAN KONFLIK SOSIAL - Afiyah Zahroh Nugeroho; Khajah Indri Saputri; Muhammad Abdullah Darraz (Titik Fokus Karya, 2026)
Islamic Religious Education (PAI) has an important role in shaping the character, morals, and social attitudes of students in the midst of diverse community life. However, the development of intolerance, radicalism, and social conflict is a challenge in the world of education. Therefore, the implementation of multicultural-based PAI is one of the relevant approaches to instill the values of tolerance, religious moderation, and mutual respect in community life. This article discusses the definition of multicultural education, multicultural-based PAI values, factors that cause radicalism and social conflict, the role of PAI teachers, multicultural learning strategies, implementation in schools, implementation challenges, and their impact on students. Through a multicultural approach, students are expected to be able to understand diversity as part of social life and have an open, tolerant, and able to coexist peacefully. Thus, multicultural-based PAI can be one of the strategic efforts in preventing the development of radical ideas and minimizing social conflicts in the educational environment and society